The Question of Provenance and the Economics of Deuteronomy: The Neo-Babylonian and Persian Periods - Richter, Sandra L. (The catholic biblical quarterly, 2020)
The provenance of Urdeuteronomium has been an essential question in biblical scholarship since the days of Julius Wellhausen. In recent years, many have turned to the Persian period to resolve this long-standing debate. This essay is the second part of a project approaching the question from an economic perspective. Assuming that the economic realities described and assumed in the Book of Deuteronomy have much to teach us regarding the book's social location, in this essay I survey the archaeologically reconstructed economies of the southern Levant in both urban and rural areas during the Neo-Babylonian and Persian eras and compare those with the literary remains of Urdeuteronomium (defined as Deut 4:44-27:26). There is particular attention to issues involving currency.